2022
DOI: 10.1177/13524585221089540
|View full text |Cite
|
Sign up to set email alerts
|

Is humoral and cellular response to SARS-CoV-2 vaccine modified by DMT in patients with multiple sclerosis and other autoimmune diseases?

Abstract: Background: The effect of disease-modifying therapies on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine response is unclear. Objectives: We aim to determine the immunological responses to SARS-CoV-2 in multiple sclerosis (MS) and anti-CD20-treated patients with other autoimmune diseases (AID). Methods: Humoral and cellular responses we determined before and 30-90 days after vaccination in patients with MS and anti-CD20-treated patients with other AID in two Catalan centers. Results: 457 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 12 publications
2
28
0
1
Order By: Relevance
“…As MS is an immune-mediated disease and DMTs alter or suppress the immune system in different ways, many recent studies have focused on the immunological responses after SARS-CoV-2 infection or vaccination. Overall, most pwMS present an immunological response after SARS-CoV-2 infection (humoral response: 76.8%-83.4%; cellular response: 59.5%) [11][12][13] or vaccination (humoral response: 74.4%-86.8%; cellular response: 62%-84.4%) [14][15][16][17] regardless of their treatment. However, it is clear by now that anti-CD20 therapies and sphingosine-1-phosphate receptor modulator (SP1RM) therapies decrease these responses.…”
Section: Two Years Of Covid-19 In the Ms Communitymentioning
confidence: 99%
See 4 more Smart Citations
“…As MS is an immune-mediated disease and DMTs alter or suppress the immune system in different ways, many recent studies have focused on the immunological responses after SARS-CoV-2 infection or vaccination. Overall, most pwMS present an immunological response after SARS-CoV-2 infection (humoral response: 76.8%-83.4%; cellular response: 59.5%) [11][12][13] or vaccination (humoral response: 74.4%-86.8%; cellular response: 62%-84.4%) [14][15][16][17] regardless of their treatment. However, it is clear by now that anti-CD20 therapies and sphingosine-1-phosphate receptor modulator (SP1RM) therapies decrease these responses.…”
Section: Two Years Of Covid-19 In the Ms Communitymentioning
confidence: 99%
“…However, it is clear by now that anti-CD20 therapies and sphingosine-1-phosphate receptor modulator (SP1RM) therapies decrease these responses. 11,[15][16][17][18] Anti-CD20 therapies impair memory B-cell production, leading to a blunted humoral response. In the study of Sormani et al, an SARS-CoV-2 serological response, after COVID-19, was observed in only 44.6% of patients on anti-CD20 therapies compared with 78.7% of the rest of patients.…”
Section: Two Years Of Covid-19 In the Ms Communitymentioning
confidence: 99%
See 3 more Smart Citations